CHRISTIANITY AND SECULARIZATION FOLLOWING THE IDEAS OF ŽELJKO MARDEŠIĆ (Религиски дијалог и соработка, 2025)
Following the interpretation of the famous Croatian sociologist Željko Mardešić (JakovJukić), this paper analyzes secularization in the context of contemporary sociology of religion.Considering various social, cultural, and religious changes, the presented secularization processis the origin of the sudden and unexpected flourishing of various forms of new religiosity and thealarming appearance of relics of the past, i.e., the increasingly present fundamentalism and integralismin major religions. According to Željko Mardešić, the secularization process consists ofthree levels and includes society, the Church, and – most deeply – the individual person. The individualfinds themselves in a strange gap. On the one hand, secularization swallows up and annulsthe sacred, while, on the other hand, the individual produces the sacred, which is not a substitutefor traditional religion, but something completely new and opposed. Željko Mardešić sees the futureof Christianity following in the footsteps of the Second Vatican Council, which seeks the effortof sincere questioning its state on the part of Christianity; to choose either political religiosity orauthentic religiosity with no political security. It is important to note that Christianity, deprived ofits many worldly roles, in the new secularization context is encouraged to focus on ritual celebrationand spiritual immersion to creatively transform society and cultural life. In this context, thereemerges an increasingly acceptable interpretation according to which, using Željko Mardešić’swords, secularization is seen as a happy event for historical Christianity, because it draws Christianitya little closer to the original evangelical truth and a more authentic living of the goodness ofits members. This event manifests in rejecting the collectivist and ideological vision of Christianityand advocates accepting the light of goodness rather than one’s own group, supporting freedomand the free human in a group defined by the community of people who believe in the person andteachings of Jesus Christ.